2000
DOI: 10.1258/0004563001899023
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of carbamazepine and carbamazepine 10,11-epoxide in breast milk and plasma by high-performance liquid chromatography

Abstract: A high-performance liquid chromatographic method was developed for the measurement of carbamazepine (CBZ) and carbamazepine 10,11-epoxide (CBZE) in human breast milk and plasma. The method involves rapid C18 solid-phase extraction of CBZ and CBZE. Chromatographic separation was achieved with a reversed-phase C8 column using a mobile phase of potassium dihydrogenphosphate (pH 2.5) and acetonitrile (67:33 v/v), with ultraviolet detection at 254 nm. 2-Methyl CBZ was used as the internal standard. Determination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…18,19 Our simple solid-phase extraction method, an efficient combination system in HPLC determination method, could remove interfering substances. [20][21][22][23] Therefore, we have examined solid-phase extraction procedures in detail for the purpose of eliminating such endogenous interference peaks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Our simple solid-phase extraction method, an efficient combination system in HPLC determination method, could remove interfering substances. [20][21][22][23] Therefore, we have examined solid-phase extraction procedures in detail for the purpose of eliminating such endogenous interference peaks.…”
Section: Discussionmentioning
confidence: 99%
“…We have reported a simple extraction method of several drugs and their metabolites by using a solid phase extraction cartridge. [20][21][22][23] However, an off-line solid phase extraction method for fluvoxamine has not been reported in previous papers. There is also no report for simultaneous determination of fluvoxamine and fluvoxamino acid in human plasma by HPLC.…”
mentioning
confidence: 99%
“…[8][9][10] However, we have shown that the C8 analytical column, which provides a more efficient resolution and a shorter analytical time than the C18 phase, has a greater efficacy for the analysis of several drugs by the HPLC method. [14][15][16] Therefore, the C8 analytical column was used for our present HPLC analytical method in plasma estazolam. The retention times for estazolam and 527 ANALYTICAL SCIENCES MAY 2002, VOL.…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported on HPLC analytical methods for several drugs by using a C8 analytical column. [14][15][16] More efficient separation and a shorter analytical time were obtained in the C8 HPLC column than in the C18 column, depending on the properties of the analytical drugs. We have appreciated the benefit of the C8 column in drug analysis by HPLC.…”
mentioning
confidence: 99%
See 1 more Smart Citation